2020
DOI: 10.3389/fcell.2020.00163
|View full text |Cite
|
Sign up to set email alerts
|

Endosome-to-TGN Trafficking: Organelle-Vesicle and Organelle-Organelle Interactions

Abstract: Retrograde transport from endosomes to the trans-Golgi network (TGN) diverts proteins and lipids away from lysosomal degradation. It is essential for maintaining cellular homeostasis and signaling. In recent years, significant advancements have been made in understanding this classical pathway, revealing new insights into multiple steps of vesicular trafficking as well as critical roles of ER-endosome contacts for endosomal trafficking. In this review, we summarize up-to-date knowledge about this trafficking p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 146 publications
2
53
0
Order By: Relevance
“…The Arp2/3 activator WASH complex is required for endosome maturation and cargo sorting 36,37 and Retromer has been shown to interact directly with the WASH complex subunit FAM21 38,39 . To investigate whether the interaction is affected in the presence of Vps35 D620N, Vps35‐GFP rescue and Vps35 D620N‐GFP rescue cells were harvested for co‐immunoprecipitation using GFPTrap agarose beads.…”
Section: Resultsmentioning
confidence: 99%
“…The Arp2/3 activator WASH complex is required for endosome maturation and cargo sorting 36,37 and Retromer has been shown to interact directly with the WASH complex subunit FAM21 38,39 . To investigate whether the interaction is affected in the presence of Vps35 D620N, Vps35‐GFP rescue and Vps35 D620N‐GFP rescue cells were harvested for co‐immunoprecipitation using GFPTrap agarose beads.…”
Section: Resultsmentioning
confidence: 99%
“…WASH is required for efficient endocytic recycling of multiple cargo proteins from endosomes to TGN or to the plasma membrane, through cooperating with retromer or retriever ( Derivery et al, 2009 ; Gomez and Billadeau, 2009 ; Puthenveedu et al, 2010 ; Zech et al, 2011 ; Gomez et al, 2012 ; Piotrowski et al, 2013 ; Phillips-Krawczak et al, 2015 ). Furthermore, recent studies showed that the WASH complex subunit FAM21 directly interacted with TGN-localized TBC1D23, thus mediating vesicle capturing at the TGN during endosome-to-TGN retrieval ( Newton et al, 2010 ; Shin et al, 2017 ; Huang et al, 2019 ; Liu et al, 2020 ; Tu et al, 2020 ).…”
Section: B Cenocepacia Effector Teca and The Wash Complexmentioning
confidence: 99%
“…The choice of degradation or recycling pathways, known as endosomal sorting, not only determines the fate of cell surface proteins, but also impacts numerous signaling pathways. As a consequence, dysregulation of endosomal sorting has been implicated in a wide range of human diseases, such as cancer, neurological disorders, and diabetes ( Small and Petsko, 2015 ; McMillan et al, 2017 ; Tu et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Na + /K + -ATPases present at the Golgi are likely not the source of Na + , since their inhibition did not affect Golgi pH in cervical cancer cells ( Llopis et al, 1998 ) and reduced Golgi resting pH in cystic fibrosis control cells ( Poschet et al, 2001 ). However, luminal Na + concentration could be driven by retrograde transport from endosomes to the trans -Golgi network, which delivers extracellular Na + obtained through endocytosis ( Tu et al, 2020 ). This process is thought to contribute to the high Na + concentrations observed in lysosomes, where Na + is the predominant cation at a concentration of ∼150 mM ( Wang et al, 2012 ; Xu and Ren, 2015 ).…”
Section: Discussionmentioning
confidence: 99%